Adición de diferentes equivalencias de balance electrolítico y su efecto en los parámetros productivos de pollos de ceba cobb 500 - Carreño Zambrano, Ángel Iván (2019)
The objective of this research was to evaluate the influence of three electrolyte balance equivalences on the response in health and productive parameters in Cobb 500 broiler chickens. 280 chickens distributed in 7 treatments were used: control T0, sodium bicarbonate T1 (NaHCO3) 240 milli equivalents (mEq / kg), sodium sesquicarbonate T2 (S-Carb) (240mEq / kg), T3 NaHCO3 (250mEq / kg), T4 S-Carb (250mEq / kg), T5 NaHCO3 (300mEq / kg) and T6 S-Carb (300mEq / kg) and 5 repetitions. The data were evaluated by ANOVA and Tukey (0.05) with the statistical package InfoStat. The variables evaluated were the weekly weight, weekly-cumulative weight gain, weekly-cumulative food consumption, abdominal fat, leg and peak pigmentation and carcass yield; in none of them were significant differences between treatments. However, the highest T5 values obtained a significant difference in the weekly-cumulative feed conversion parameter with respect to the other treatments 1.53 ± 2.38 g (P value => 0.05) for the weekly weight parameters with 2910 ± 1.06 g, weekly-cumulative weight gain 679 ± 0.02 g and yield of the channel 81.65%. In relation to the benefit-cost, treatments T1, T3 and T5 were superior to the other treatments ($ 0.19, 0.19 and 0.23 respectively). It is concluded that the use of levels of 300mEq / kg of sodium bicarbonate improves the feed conversion in the productive parameters in Cobb 500 chickens.